Is Breast Size Related to Prevalent Thoracic Vertebral Fracture? A Cross-Sectional Study. - Spencer, Linda; McKenna, Leanda; Fary, Robyn; Ho, Richard; Briffa, Kathy (American Society for Bone and Mineral Research, 2020)
Large breasts may increase the likelihood of thoracic vertebral fractures by increasing the mechanical loading of the spine. We examined breast size as a factor associated with prevalent thoracic vertebral fractures, also considering its relationship with thoracic kyphosis and upper back extensor muscle endurance. Using a cross-sectional study, the design measurements collected were thoracic vertebral fractures (≥20% loss in vertebral body height on lateral radiograph), breast size (bra size converted to an ordinal breast size score), BMD (g/cm2 averaged femoral neck, DXA), upper back extensor muscle endurance (isometric chest raise test), body composition (DXA), thoracic kyphosis (radiograph), and upper back pain (numerical rating scale). Correlations and multivariable logistic regression examined relationships between characteristics and their association with vertebral fracture. Participants were 117 healthy postmenopausal women. The 17 (15%) women with ≥1 thoracic vertebral fracture had larger breast size (mean difference [MD]: 2.2 sizes; 95% CI, 0.6 to 3.8 sizes), less upper back extensor muscle endurance (MD: -38.6 s; 95% CI, -62.9 to -14.3 s), and greater thoracic kyphosis (MD: 7.3°; 95% CI, 1.7° to 12.8°) than those without vertebral fracture. There were no between group differences in age, height, weight, and BMD. Breast size (r = -0.233, p = 0.012) and thoracic kyphosis (r = -0.241, p = 0.009) correlated negatively with upper back extensor muscle endurance. Breast size was unrelated to thoracic kyphosis (r = 0.057, p = 0.542). A (final) multivariable model containing breast size (OR 1.85; 95% CI, 1.10 to 3.10) and thoracic kyphosis (OR 2.04; 95%CI, 1.12 to 3.70) explained 18% of the variance in vertebral fracture. Breast size had a significant, but weak relationship with vertebral fracture (R2 = 0.10), which was independent of BMD and unrelated to thoracic kyphosis. Further work is needed to confirm larger breast size as a risk factor for vertebral fracture. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.